What is the Real Cost of Intraoperative Floppy Iris Syndrome in Cataract Surgery? - Tzamalis, Argyrios; D. Christou, Chrysanthos; Prousali, Efthymia; Ziakas, Nikolaos (Journal of ophthalmic & vision research, 2023)
This is a Letter and does not have an abstract. Please download the PDF or view the article in HTML.